MODERN IDEAS ABOUT "ATOPIC MARCH" PATHOGENESIS AND POSSIBLE ROLE OF HEAT-SHOCK PROTEINS - N. M. Ivanova; N. N. Cybikov; I. N. Sormolotova (State Scientific Center of Dermatovenereology and Cosmetology, 2018)
Allergic diseases pose a serious health problem worldwide. The review of literature presents some data on the role of heat shock proteins in the pathogenesis of atopic dermatitis and allergic rhinitis, as the most common diseases in the population of this nosological group. Data on the possible role of heat shock proteins in the pathogenesis of atopic march development are also presented.